Clostridium perfringens Is Not Suitable for the Indication of Fecal Pollution from Ruminant Wildlife but Is Associated with Excreta from Nonherbivorous Animals and Human Sewage - Vierheilig, J. (American Society for Microbiology, 2013)
During a 3-year study, Clostridium perfringens was investigated in defined fecal sources from a temperate alluvial backwater area of a large river system. The results reveal that using C. perfringens as a conservative water quality indicator for total fecal pollution monitoring is no longer justified but suggest that it can be used as a tracer for excreta from nonherbivorous wildlife and human sewage.